SISTEMA DE EVALUACION Y ACREDITACION PARA LA CARRERA DE ESTOMATOLOGIA System of evaluation and accreditation for the Dentistry career - Luis Suárez Rosas; Irene Barrios Osuna; María Elena González Espíndola (Universidad de Ciencias Médicas de La Habana, 2008)
Se plantea la conveniencia de establecer un Sistema de Evaluación y Acreditación para la Carrera de Estomatología adecuado a las particularidades de esta carrera universitaria y los escenarios docentes donde se desarrolla la misma en el Sistema Nacional de Salud de Cuba. Se comentan aspectos de la investigación que se realiza para complementar las variables de calidad establecidas por el Sistema de Evaluación y Acreditación de Carreras Universitarias (SEA-CU) con variables de calidad, indicadores y criterios de evaluación propias de la Carrera de Estomatología. In this paper is analyzed the convenience of the establishment of an Evaluation and Accreditation System for the career of Dentistry adequate to the particularities of this university career and their teaching scenes where it is developed in the Health National System of Cuba. Some aspects of the research that is realized at the present are commented in order to complement the quality variables established by the Evaluation and Accreditation of University Careers System (SEA-CU) with quality variables, indicators and evaluation criterions owns of the career of Dentistry.